2020
DOI: 10.18203/issn.2454-5929.ijohns20200149
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study to evaluate the impact and independency of depth of invasion in comparison with other clinicopathologic prognostic variables in oral cavity malignancy

Abstract: Background: Depth of invasion is included in the staging of oral cavity malignancies in the recent 8 th edition of American Joint Committee on Cancer or tumour, node and metastasis staging system. This study analyses the impact of diffuse optical imaging (DOI) on incidence of lymph node involvement, stage migration, postoperative margin and independency. Methods: Postoperative HPE of fifty patients with oral cavity malignancy operated in our institute from January 2018 were collected. Depth of invasion and oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Few smaller studies have shown DOI as an independent predictor for survival in T3 OSCC. 5,6 When AJCC stage III OTSCC is considered where more variables are present (node positivity), heterogeneity increases, and therefore more sub-groups may have different survival. The study aims at establishing DOI as an independent predictor across different sub-groups of AJCC stage III OTSCC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few smaller studies have shown DOI as an independent predictor for survival in T3 OSCC. 5,6 When AJCC stage III OTSCC is considered where more variables are present (node positivity), heterogeneity increases, and therefore more sub-groups may have different survival. The study aims at establishing DOI as an independent predictor across different sub-groups of AJCC stage III OTSCC.…”
Section: Introductionmentioning
confidence: 99%
“…The difference in prognosis between these sub‐groups is yet to be determined. Few smaller studies have shown DOI as an independent predictor for survival in T3 OSCC 5,6 . When AJCC stage III OTSCC is considered where more variables are present (node positivity), heterogeneity increases, and therefore more sub‐groups may have different survival.…”
Section: Introductionmentioning
confidence: 99%